2015
DOI: 10.1007/s11224-015-0646-0
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular interactions in polymorphs of the cyclic trimeric perfluoro-ortho-phenylene mercury from geometric, energetic and AIM viewpoints: DFT study and Hirshfeld surface analysis

Abstract: Macrocyclic polydentate Lewis acids are of ongoing interest owing to their ability for molecular recognition of anions; however, deep understanding of the nature of supramolecular bonding in their crystals is still lacking. To solve this problem, we have analysed four polymorphic modifications A-D of cyclic trimeric perfluoro-ortho-phenylene mercury (1) by quantum chemical calculations of intermolecular pair interactions energy. In all polymorphs, the main structural motif is stacked columns, which are further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The presence of an extended -system creates preconditions for the formation of stacking interactions which is soft enough to provide a shift of the stacked molecules. Such molecules are capable of forming a large number of polymorphic modifications (Shtukenberg et al, 2017;Dolgushin et al, 2016;Shishkina et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an extended -system creates preconditions for the formation of stacking interactions which is soft enough to provide a shift of the stacked molecules. Such molecules are capable of forming a large number of polymorphic modifications (Shtukenberg et al, 2017;Dolgushin et al, 2016;Shishkina et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has proved to be more informative in studying the structure of crystals and the role of intermolecular interactions of different types in their formation. This approach is the most useful in comparing polymorphic modifications (Dolgushin et al, 2016;Shishkina et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…A comparison of polymorphs, solvates, and co-crystals of such compounds gives a key for better understanding of these factors. For example, an analysis of 88 crystal structures containing trimeric perfluoro-ortho-phenylen mercury (TPPM) revealed only four motifs of their packing with Lewis bases, governed mainly by Hg...C and π...π interactions [80]. It was shown that the type of supramolecular motif strongly correlates with the nature of a co-former.…”
Section: Studyingcrystal Packing Featuresmentioning
confidence: 99%
“…For example, the binary stacks of TPPM and aromatic molecules can be found in a series of co-crystals with luminescent properties [72]. This motif, one of four typical for TPPM co-crystals [80], can be constructed from a TPPM molecule and two aromatic C 6 rings situated above and below the TPPM meanplane ( Figure 3a). The Crystal Packing Feature search allows us to extract from the CSD other examples of such potentially luminescent co-crystals, and to compare the distances between the meanplanes of planar molecules as a measure of charge transfer from electron-rich aromatic molecules to anticrowns.…”
Section: Studyingcrystal Packing Featuresmentioning
confidence: 99%
See 1 more Smart Citation